Optimization of the Turbine Grids Using Geometric Quality Criteria for Circumscription of the Profile and Channel - Boiko, Anatoly; Usaty, Alexander Pavlovitch; Barannik, Valentine (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
<span style="color: black; font-family: 'Times New Roman'; font-size: 9pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">The multi-criteria optimization method of the turbine grids using the geometric quality criteria of circumscription of the turbine profiles and channels, created by them, is developed. The article presents the features of the proposed methodology and the mathematical description of the proposed complex of geometric criteria that describes the quality of the turbine grids. The method of optimization as well as convolution algorithms and regulation of geometric quality criteria complex has been described. The article presents the results of the optimization of three turbine grids. The results of comparative research of efficiency of optimal turbine grids, obtained using the proposed method of optimization, and the turbine grids built using the initial profiles P2 are given. A higher efficiency of the optimal turbine grids has shown and the physical nature of the results was explained. Because of the complex criteria of quality and quantity parameters, that have influence on the efficiency of turbine profile cascades, objective function is multimodal. Due to the high efficiency of the original profiles, the values of optimal profiles in extreme locations differ slightly. Therefore, the search for the best solution (global extremum point) demanded the combination of several methods for finding optimal solutions.